(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2018)
This paper aims to reconstruct how the Membranaceous Section of the Historical Diocesan Archive of Taranto was formed. The research got underway with the observation of many archival interventions on the verso of the oldest 250 parchments deeds stored in the archive, dating from the second half of the 12th to the end of the 14th century. Then, these interventions have been registered and attributed to some archivists, often anonymous, working between the 14th and the 20th century. The data obtained in such a way have been then compared to other important sources kept in the same archive, such as the inedited chronicle of the Holy Visit of Lelio Brancaccio, Archbishop of Taranto, written between 1575 and 1577, and some paper inventories compiled during several reorganizations of the Membranaceous Section that occurred over time. DOI 10.17464/9788867742684